Turkish Society of Pediatric Emergency and Intensive Care Medicine Neurocritical Care Study Group Stroke in Critically Ill Children - Feyza İnceköy Girgin; Mutlu Uysal Yazıcı; Serhan Özcan; Fulya Kamit; Pınar Yazıcı Özkaya; Çelebi Kocaoğlu; Resul Yılmaz; Eylem Ulaş Saz; Agop Çıtak (Journal of Pediatric Emergency and Intensive Care Medicine)
Stroke is a disease whose differential diagnosis is not easy because its symptoms and signs can be seen in many neurologic diseases. When neurological examination, clinical findings and radiological imaging are evaluated together, neurological complications can be minimized with early diagnosis and treatment. Our aim is to increase stroke awareness by emphasizing the importance of time in pediatric acute stroke management and to remind the role of stroke team formation and multidisciplinary approach in early diagnosis and treatment.